2018
DOI: 10.1111/wre.12331
|View full text |Cite
|
Sign up to set email alerts
|

Understanding dormancy breakage and germination ecology of Cynara cardunculus (Asteraceae)

Abstract: Summary Cynara cardunculus is a troublesome weed in temperate grazing lands. Cynara cardunculus achenes are usually dormant at dispersal and require alternating temperatures to terminate dormancy and germinate. Laboratory and glasshouse experiments were conducted to determine (i) the treatments able to terminate dormancy and (ii) the effect of environmental factors and agronomic practices on germination and emergence of non‐dormant (dry after‐ripened) achenes. Scarification, hydrogen peroxide and sodium hypoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Maximum germination increased to day 6 and no further germination was scored until the end of the experiment. These results are in line with the previous studies using dry after-ripened wild cardoon achenes, confirming that this treatment can be used for dormancy alleviation in this plant [ 24 , 46 ].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Maximum germination increased to day 6 and no further germination was scored until the end of the experiment. These results are in line with the previous studies using dry after-ripened wild cardoon achenes, confirming that this treatment can be used for dormancy alleviation in this plant [ 24 , 46 ].…”
Section: Resultssupporting
confidence: 91%
“…This was performed to preserve the physiological state of achenes and to prevent ageing. To alleviate achene dormancy and to analyze the effect of different temperature regimes on dormancy termination, for all the tests performed in the present study, we used dry after-ripened achenes at 35 °C for 21 days as reported in greater detail in Huarte et al [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In seed ecology, temperature has a dual role. It affects dormancy as well as seed germination [ 40 , 41 ]. S. lanceolatum seeds ripen in late November or early December when their dispersal begins and lasts throughout the winter.…”
Section: Discussionmentioning
confidence: 99%